Can associative memory be modeled by quantum information? - Siomau, Michael (Frontiers in Applied Mathematics and Statistics, 2025)
Associative memory is the ability to reveal similarities between unrelated items. Models of associative memory typically rely on significant assumptions about information encoding procedure, structure of underlying complex network, computational power of nodes, and communication capacity of links. Keeping assumptions plausible and at minimum, the search for association can be done on a network enhanced with quantum information processing exploiting non-locality and quantum state comparison.